2004
DOI: 10.17221/5700-vetmed
|View full text |Cite
|
Sign up to set email alerts
|

New records of Ascaridia platyceri (Nematoda) in parrots (Psittaciformes)

Abstract: ABSTRACT:The aim of the study was to determine the range of species of ascarids in parrots in the Czech Republic. Ascarids were found during post-mortem parasitological examination of 38 psi�aciform birds belonging to 15 different species. All ascarids found were determined as Ascaridia platyceri. Nine bird species were determined as new hosts of this parasite. A. platyceri is a typical ascarid for parrots of Australian origin. The fact that this parasite was found in bird species of African origin demonstrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…In cases where parrots of different origin are kept together, the parasites can apparently also infect hosts that are not of the relevant zoogeographical origin. This phenomenon was confirmed by the detection of A. hermaphrodita in parrots of Oriental origin kept in South America (Travassos, 1930;Canavan, 1931), and A. platyceri in parrots of Neotropical and Afrotropical origin kept in Germany (Hartwich and Tscherner, 1979) and in the Czech Republic (Kajerova et al, 2004).…”
Section: Resultsmentioning
confidence: 73%
See 2 more Smart Citations
“…In cases where parrots of different origin are kept together, the parasites can apparently also infect hosts that are not of the relevant zoogeographical origin. This phenomenon was confirmed by the detection of A. hermaphrodita in parrots of Oriental origin kept in South America (Travassos, 1930;Canavan, 1931), and A. platyceri in parrots of Neotropical and Afrotropical origin kept in Germany (Hartwich and Tscherner, 1979) and in the Czech Republic (Kajerova et al, 2004).…”
Section: Resultsmentioning
confidence: 73%
“…(Nixton and Weeks, 1985) and in A. personatus Reichenow, 1887(Weeks, 1981 in New Zeland too. This parasite has been commonly found in the Czech Republic (Kajerova et al, 2004). New hosts among Australian parrots kept in captivity were Alisterus scapularis (Lichtenstein, 1818), Barnardius zonarius (Shaw, 1805), Cacatua sulphurea (Gmelin, 1788), and C. ducorpsii (Pucheran, 1853).…”
Section: Ascaridia Platyceri (Hartwich and Tscherner 1979)mentioning
confidence: 99%
See 1 more Smart Citation
“…However, A. platyceri differ morphologically from the present Ascaridia species in view of the presence of interlabium, absence of spicular alae and the number of caudal papillae (Tables 1 and 2). Moreover, the positions and sizes of caudal papillae were clearly different from each other (each papilla is large, obvious and stocky in A. platyceri) (Kajerova et al 2004a(Kajerova et al , 2004b. Partial 18S rDNA sequencing analysis showed that the present Ascaridia species was closely related with A. galli and A. numidae.…”
Section: Discussionmentioning
confidence: 85%
“…Seven Ascaridia species (Ascaridia galli, Ascaridia columbae, Ascaridia hermaphrodita, Ascaridia sergiomeirai, Ascaridia ornate, Ascaridia nicobarensis and Ascaridia platyceri) have been reported in birds of the order Psittaciformes (Kajerova et al 2004a). Discrimination among those species was achieved according to observations of subtle morphological differences such as the number and position of caudal papillae, presence or absence of spicular alae and interlabia, position of the vulva and tail length (Avcioglu et al 2008;Hartwich and Tscherner 1979;Kajerova et al 2004aKajerova et al , 2004bKung 1949;Mines 1979). However, morphometric characteristics among those species are overlapped.…”
Section: Introductionmentioning
confidence: 99%